2023
DOI: 10.3390/ph16060847
|View full text |Cite
|
Sign up to set email alerts
|

Sucrosomial® Iron: An Updated Review of Its Clinical Efficacy for the Treatment of Iron Deficiency

Abstract: Iron deficiency (ID) and iron deficiency anemia (IDA) are highly prevalent worldwide. Oral iron salts, especially ferrous sulfate, are commonly used for the treatment of iron deficiency (ID). However, its use is associated with gastrointestinal side effects, thus compromising treatment compliance. Intravenous iron administration is a more costly and logistically complex alternative and is not risk-free, as infusion and hypersensitivity reactions may occur. Sucrosomial® iron is an oral formulation consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 120 publications
0
1
0
Order By: Relevance
“…21 In addition, newer oral iron formulations, such as ferric maltol or sucrosomial iron, have been postulated to be absorbed differently than standard iron salt compounds and have been associated with excellent therapeutic success likely due to improved enteral absorption that is less affected by hepcidin-a systemic iron regulator that modulates enteral iron absorption and systemic iron availability. [22][23][24][25][26] In contrast to standard iron salt compounds, iron from these newer formulations does not readily dissociate, resulting in lower levels of free luminal iron and, consequently, fewer side effects. 23 24 26 Nevertheless, oral iron therapy in active disease states remains controversial.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition, newer oral iron formulations, such as ferric maltol or sucrosomial iron, have been postulated to be absorbed differently than standard iron salt compounds and have been associated with excellent therapeutic success likely due to improved enteral absorption that is less affected by hepcidin-a systemic iron regulator that modulates enteral iron absorption and systemic iron availability. [22][23][24][25][26] In contrast to standard iron salt compounds, iron from these newer formulations does not readily dissociate, resulting in lower levels of free luminal iron and, consequently, fewer side effects. 23 24 26 Nevertheless, oral iron therapy in active disease states remains controversial.…”
Section: Open Accessmentioning
confidence: 99%
“…[22][23][24][25][26] In contrast to standard iron salt compounds, iron from these newer formulations does not readily dissociate, resulting in lower levels of free luminal iron and, consequently, fewer side effects. 23 24 26 Nevertheless, oral iron therapy in active disease states remains controversial. Murine studies showed that oral iron might exacerbate underlying disease due to excess enteral iron, which alters the intestinal microbiota and increases oxidative stress.…”
Section: Open Accessmentioning
confidence: 99%
“…However, approximately 50% of those taking oral iron report gastrointestinal (GI) side effects, which can lead to decreased tolerance and reduced compliance with iron supplementation [24,25]. In recent years, iron preparations with different pharmacokinetics such as microencapsulated iron and sucrosomial iron have been used for ID [26,27]. These preparations are reported not to cause side effects such as GI irritation, often associated with iron salts.…”
Section: Introductionmentioning
confidence: 99%